Jerusalem within these walls - Birch, Miriam ([S.l.] : National Geographic Society [production company] ; Kuala Lumpur : Videomaster Film [distributor], 1986)
The story of the greatest city, Jerusalem, the symbol of peace and where the people of different culture lives side by side together
Executive producer, Hyman Kaufman ; editor, Dennis B. Kane, Thomas Skinner
Narrator: Christopher Plummer
Keywords: Jerusalem -- History; Jerusalem -- Social life and customs